ANALISIS FAKTOR RISIKO PENYEBAB ANEMIA PADA IBU HAMIL DI PUSKESMAS WILAYAH KABUPATEN BANJARNEGARA TAHUN 2018 - Ratih Subekti; Dewie Sulistyorini (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2018)
Anemia in pregnant women is a condition in which a pregnant woman experiences iron deficiency in her blood. WHO establishes the incidence of pregnant anemia ranging from 20% to 89% by determining Hb 11 gr% as the basis. The impact of anemia on pregnancy can occur abortion, labor prematurity, obstacles to fetal growth and development in the uterus and antepartum bleeding. Several factors that can cause anemia in pregnancy include gravida, age, parity, education level, economic status and compliance with consumption of Fe tablets. The purpose of this study was to find out the risk factors of anemia in pregnant women in public health centers in Banjarnegara on 2018. The research method was analytical surveys with cross sectional approaches. Sampling is based on total sampling totaling 50 people. The results showed that the majority were in the